First Years in Nursing: Relationship and Risk Factors Between Reality Shock and Attitudes Toward Medical Errors - Duru Berra Harman; Muzaffer Berna Doğan (The Journal of Continuing Education in Nursing, 2026)
Background: This study examined the relationship between reality shock and attitudes toward medical errors in newly graduated nurses. Method: A descriptive and correlational design was used. Data were obtained from 300 nurses with 3 to 24 months of experience. Information was collected with the personal information form, Reality Shock Scale, and Medical Error Attitude Scale. Results: Reality shock was positively correlated with medical error perception (cognitive perception of medical errors), approach, and reasons. Higher Reality Shock Scale scores were associated with unwillingness to work in clinics, mixed shifts, dissatisfaction, and limited support. Scores on the Medical Error Attitude Scale were positively related to professional knowledge and responsibility. Working in university or emergency settings and reporting all errors improved attitudes, whereas mixed shifts and heavy workloads reduced attitudes. Conclusion: For new nurses, reality shock negatively affects error awareness (sensitivity to error-related situations in practice) and willingness to report errors. Supportive education and mentorship can ease this transition and encourage a culture of error reporting.